Synergistic effects of surface chemistry and porosity in vanadium redox reactions: from smooth thin films to high surface area carbon electrodes - Colavita, Paula; Costa de Oliveira, Maida (My University, 2025)
Vanadium redox flow batteries (VRFB) are promising devices for energy storage. However, sluggish kinetics at conventional porous carbon electrodes can limit efficiency, thus prompting interest in N-functionalization for improving performance. Herein synergistic impacts of changes in wettability and chemical reactivity arising from surface pyridinic-N functionalities are investigated. First, fabrication of model carbon electrodes with smooth topography and disk geometry, grafted with pyridyl groups at varying coverage is reported. These are used to unambiguously determine the impact of pyridinic-N sites on the intrinsic activity of carbon surfaces towards VO2+/VO2+ reactions. Combined voltammetry and finite element simulations provided estimates of heterogeneous charge-transfer constants, k0, which increase by up to 50-fold upon pyridyl grafting. Pyridyl groups also increase wettability however this is not sufficient to improve charge-transfer kinetics at carbon: indeed, treatments that increase hydrophilicity without grafting pyridyl groups yield no change in k0. The impact of pyridyl grafting at porous carbon collectors is then investigated using voltammetry and VRFB tests. Results indicate that wettability changes overwhelmingly determine the response and obscure the effects of pyridinic-N on intrinsic activity. All surface treatments that increase wettability lead to comparable responses, thus evidencing key challenges in applying chemical design principles to complex carbon electrode architectures.
PUBLISHED
Keywords: Nanoscience & Materials; Catalysis/Kinetics; Mechanisms of reactions; Nanotechnology